The Secret Code of the Galician Land Between the Two Rivers: Spacetime Organization of Yuri Andrukhovych’s Essays - Maftyn, Natalia (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The paper deals with the spacetime aspect of the essays by Yu. Andrukhovych (‘Disorientation in Locality’ in particular); it is both a feature and an efective strategy used by the author in order to structure his text and organize its imagery. Other distinctive features of Andrukhovych’s essays are inner dynamics of artistic images, a complex associative network, paradox as a way of playing with a reader, constant switching from sociohistorical time to private chronotope of personal world view. Looking at European culture from different spacetime perspectives and, at the same time, feeling its contemporary pulsation, marking his private narrative cardiogram with philosophical and historical ‘splash-ups’, the author manages to communicate his idea of Central Europe as a tradition, in which Ukraine has its share. The text of ‘Disorientation in Locality’ is modelled in the dimensions of different spacetime continuums; due to this, the discussed locuses reveal themselves as palimpsests of cities and places – geological cuttings of different temporal layers, whose deep textual meanings shine through the surface of the author’s narrative. Into the fabric of sociohistorical time, Andrukhovych weaves idyllic chronotope of early times (‘an Austrian-Hungarian myth’ tinged with the author’s humour, the mystic locus of the Carpathians) complementing it with his private spacetime chronotope, generic memory. According to the author, the chronotope of apocalypse is destroying the Tradition; though the message of his essays is revealing the possibility of the two-way movement along the sociohistorical temporal vector, which ensures continuity of tradition and historism.